2013
DOI: 10.1097/eja.0b013e32835a1127
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine induces a hyperthermic and hypermetabolic crisis in pigs with and without a genetic disposition for malignant hyperthermia

Abstract: MDMA is not a classic trigger for the development of malignant hyperthermia reactions in pigs. MDMA intoxication leads to severe, long-lasting hyperthermia and hypermetabolism in both malignant hyperthermia-susceptible and hyperthermia-normal pigs, with life-threatening malignant hyperthermia-like symptoms which are responsive to supportive treatment and dantrolene sodium suspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Similar to what has been observed with MDMA toxicity in rodent models, MH susceptible adrenalectomized pigs were also more resistant to MH toxicity, 109 and treatment with thyroid hormone led to an earlier onset of MH in pigs, 110 implicating activation of the hypothalamic-pituitary-adrenal and -thyroid axes in MH. Despite the similarities, a recent study done by Schutte et al 111 . to investigate whether MDMA could trigger MH in susceptible pigs found that there were no metabolic differences between MH-susceptible pigs and MH-normal pigs following MDMA exposure.…”
Section: Ucp Hyperthermia Versus Ryr1 “Malignant Hyperthermia”mentioning
confidence: 98%
“…Similar to what has been observed with MDMA toxicity in rodent models, MH susceptible adrenalectomized pigs were also more resistant to MH toxicity, 109 and treatment with thyroid hormone led to an earlier onset of MH in pigs, 110 implicating activation of the hypothalamic-pituitary-adrenal and -thyroid axes in MH. Despite the similarities, a recent study done by Schutte et al 111 . to investigate whether MDMA could trigger MH in susceptible pigs found that there were no metabolic differences between MH-susceptible pigs and MH-normal pigs following MDMA exposure.…”
Section: Ucp Hyperthermia Versus Ryr1 “Malignant Hyperthermia”mentioning
confidence: 98%
“…In addition, dantrolene is used in case of 3,4-methylenedioxymethamphetamine (MDMA, 'ecstasy') overdose too [18]. Notably, there is already one published trial on successful DSS use in MDMA overdose in swine [19]. Further trials would be eligible.…”
Section: Expert Opinionmentioning
confidence: 99%
“…booster or high doses)Green et al (2004);Parrott (2012);Schütte et al (2013);Topp et al (1999) Prolonged and vigorous dancing in hot settings during "rave" dance partiesDafters (1995); Docherty and Green (2010); Kiyatkin et al (2014); Parrott et al (2006); Suy et al (1999); Winstock et al (2001) Reduced fluid intake and dehydration Bouchama and Knochel (2002); Coris et al (2004); Montain and Coyle (1992); Sawka (1992); Sawka et al (1985) Co-use of MDMA and alcohol Calle et al (2019); Calle et al (2018); Horyniak et al (2014); Liechti et al (2005); Palamar et al (2019); Rogers et al (2009); Roxburgh and Lappin (2020); Schifano (2004); Schifano et al (2003) Hyperthyroidism Sprague et al (2018)…”
mentioning
confidence: 99%